2021
DOI: 10.1177/13540688211021053
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination by politicians against religious minorities: Experimental evidence from the UK

Abstract: Are Labour party politicians anti-Semitic, and are Conservative party politicians Islamophobic? In this correspondence study we measure the responsiveness of elected local representatives in the United Kingdom to requests from putative constituents from minority religious groups. We send short email requests to 10,268 local government representatives from each of the main political parties, from stereotypically Islamic, Jewish, and Christian names. Response rates are six to seven percentage points lower to ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…9 Even in developed countries such as the UK, religious minorities face discriminatory treatment by politicians. 10 Various violations and discrimination against religious minorities are intertwined with differences in culture, ethnic origin, gender, and language.…”
Section: Introductionmentioning
confidence: 99%
“…9 Even in developed countries such as the UK, religious minorities face discriminatory treatment by politicians. 10 Various violations and discrimination against religious minorities are intertwined with differences in culture, ethnic origin, gender, and language.…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2017 British Social Attitudes Survey, 33 percent of Conservative party supporters would characterize themselves as at least moderately racist, compared to 18 percent of Labor party supporters. 8 According to a survey, most black people in the United Kingdom have encountered bias from medical professionals due to their race, with younger people reporting this prejudice more frequently. A poll revealed that 65% of black respondents had encounterediscrimination from medical professionals, including doctors and other staff members, which percentage is higher among black people aged 18 to 34 with 75%.…”
Section: A Introductionmentioning
confidence: 99%
“…Such issues emerged discernibly over the research project led by Rosie Campbell in 2021 (Campbell and Bolet 2022). This study randomly assigned e-mails from different kinds of fictitious constituents to UK Members of Parliament (MPs), using a method pioneered in the USA by Butler, Broockman and others (Butler and Broockman 2011;Butler and Nickerson 2011;Butler 2014), and widely applied in many other jurisdictions (McClendon 2016;Vries, Dinas, and Solaz 2016;Habel and Birch 2019;Crawfurd and Ramli 2021). The difference to other studies was the requirement by the university's Research Ethics Committee to carry out a debriefing after the experiment had taken place.…”
mentioning
confidence: 99%